Usos, propriedades físico-químicas, nutricionais e tecnologias do tucupi: uma revisão - RAIOL, Jessica Agnes Gaignoux (2023)
Tucupi is a beverage resulting from the fermentation process of manipueira, a by product of cassava (Manihot esculenta Crantz), has sensory characteristics and eccentric composition, marked by yellowish color, acidic flavor, characteristic aroma, and numerous forms of culinary preparation which range from sauces, risottos de tucupi with jambu, even tacacá, which is the combination of indigenous soup, mani poi, enriched with ingredients from colonizers and African peoples. This food has high levels of cyanogenic compounds, as well as bacteria (BAL) and yeasts that participate in the symbiosis of its fermentation. In addition to its production generate income for the population. The objective of this work was to carry out a complete literature review on tucupi, exploring the literature to date about the physical-chemical, nutritional characteristics, toxic and beneficial properties, even its origin and method of preparation. Highlighting the knowledge and technologies used to prepare this drink, as well as the pre-established safety parameters and standardization of the production of tucupi by the Agricultural Defense Agency of Pará.